2020
DOI: 10.1186/s13075-020-02189-w
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Sjogren’s syndrome reduces the probability of reaching target in rheumatoid arthritis patients: a propensity score matched real-world cohort from 2009 to 2019

Abstract: Background: Overlapping Sjogren's syndrome (SS) is not uncommon in rheumatoid arthritis (RA) and considered as a probable detrimental factor of RA. But data on the impact of overlapping SS on RA therapeutic response is limited. Our current study aimed to identify the effect in a real-world cohort from 2009 to 2019. Methods: The medical records of RA patients who visited the rheumatology clinic of our medical center from 2009 to 2019 were reviewed. Their composite disease activity scores at each follow-up point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The cohort, first established over a decade ago, has been described in greater detail in our previous researches. [16][17][18][19][20][21] Briefly, demographics, symptom duration, RA core set variables, laboratory findings and treatment details were documented at the initial visit in the database. After that, all patients are prospectively followed up and documented at least 3 monthly for those in moderate/high diseases activity and every 3-12 months (usually 3-6 months) for those in remission/low disease activity (LDA).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The cohort, first established over a decade ago, has been described in greater detail in our previous researches. [16][17][18][19][20][21] Briefly, demographics, symptom duration, RA core set variables, laboratory findings and treatment details were documented at the initial visit in the database. After that, all patients are prospectively followed up and documented at least 3 monthly for those in moderate/high diseases activity and every 3-12 months (usually 3-6 months) for those in remission/low disease activity (LDA).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…[13] The current study shows a higher prevalence of RA as a cause of sSS, and RA patients with sSS had worse joint damage, suggesting that sSS may be a marker of more aggressive disease. [14,15] Sicca symptoms were more prevalent among patients diagnosed with sSS than pSS [Table 1]. Brito-Zerón et al [16] found higher frequency Sicca symptoms to be the most common manifestation of SS, with up to 98% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were identified from the outpatient clinic of our department in real-world longitudinal database, which has been previously described and approved by the local ethics committee [ 5 , 12 , 16 , 17 ]. In brief, a longitudinal database of a large cohort of RA patients had been established over the course of more than 10 years.…”
Section: Methodsmentioning
confidence: 99%